Microvascular dysfunction following cardiopulmonary bypass plays a central role in postoperative organ dysfunction - Kant, Shawn; Banerjee, Debolina; Sabe, Sharif A.; Sellke, Frank; Feng, Jun (Frontiers in Medicine, 2023)
Despite significant advances in surgical technique and strategies for tissue/organ protection, cardiac surgery is a profound stressor on the human body and is associated with numerous intraoperative and postoperative collateral effects across different tissues and organ systems. Of note, cardiac surgery has been shown to induce significant alterations in microvascular reactivity. This involves altered myogenic tone, altered microvascular responsiveness to many endogenous vasoactive agonists, and generalized endothelial dysfunction across multiple vascular beds. This review begins with a survey of in-vitro studies that examine the cellular mechanisms of microvascular dysfunction following cardiac surgery, with a focus on endothelial activation, weakened barrier integrity, altered cell surface receptor expression, and changes in the balance between vasoconstrictive and vasodilatory mediators. Microvascular dysfunction in turn influences postoperative organ dysfunction in complex, poorly understood ways. Hence the second part of this review will highlight in-vivo studies examining the effects of cardiac surgery on critical organ systems, notably the heart, brain, renal system, and skin/peripheral tissue vasculature. Clinical implications and possible areas for intervention will be discussed throughout the review.